2011
DOI: 10.1371/journal.pone.0015859
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Load: The Main Factor for Altered Gene Expression in Right Ventricular Hypertrophy in Chronic Hypoxic Rats

Abstract: BackgroundThe present study investigated whether changes in gene expression in the right ventricle following pulmonary hypertension can be attributed to hypoxia or pressure loading.Methodology/Principal FindingsTo distinguish hypoxia from pressure-induced alterations, a group of rats underwent banding of the pulmonary trunk (PTB), sham operation, or the rats were exposed to normoxia or chronic, hypobaric hypoxia. Pressure measurements were performed and the right ventricle was analyzed by Affymetrix GeneChip, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 48 publications
5
28
0
Order By: Relevance
“…32 Independent studies from our lab and others have suggested that TG2mediated fibrosis is implicated in several physiological conditions that are associated with enhanced tissue glycolysis and metabolic dysfunction. 32 Independent studies from our lab and others have suggested that TG2mediated fibrosis is implicated in several physiological conditions that are associated with enhanced tissue glycolysis and metabolic dysfunction.…”
Section: Discussionmentioning
confidence: 97%
“…32 Independent studies from our lab and others have suggested that TG2mediated fibrosis is implicated in several physiological conditions that are associated with enhanced tissue glycolysis and metabolic dysfunction. 32 Independent studies from our lab and others have suggested that TG2mediated fibrosis is implicated in several physiological conditions that are associated with enhanced tissue glycolysis and metabolic dysfunction.…”
Section: Discussionmentioning
confidence: 97%
“…A blood sample was collected in a microcapillary tube and centrifuged (International equipment company, micro-capillary centrifuge model M B) for three hours as previously described [36].…”
Section: Methodsmentioning
confidence: 99%
“…More recently, Baandrup et al [ 58 ] showed that the expression in the RV of the same 172 genes participating in fatty acid oxidation and the glycerol channel was altered in the chronic hypoxia or rats with banding of the pulmonary trunk (PTB). Only 11 genes (e.g.…”
Section: The Right Ventricle In Animals At High Altitudementioning
confidence: 99%